Minimizing Unnecessary Interventions During Labor and Birth. Issue 4 (July 2017) - Simpson, Kathleen Rice
Abstract : A call to minimize unnecessary interventions during labor and birth for healthy low risk women in spontaneous labor by our colleagues at the American College of Obstetricians and Gynecologists is most welcome and has been endorsed by the American College of Nurse-Midwives and the Association of Women's Health, Obstetric, and Neonatal Nurses.